P212 Screening for lung cancer: a qualitative study of the acceptability of screening and participation in the lung-SEARCH trial. (16th November 2010) - Akporobaro, A; Patel, D; Chinyanganya, N; Butawan, R; Hackshaw, A; Seale, C; Spiro, S; Griffiths, C
Abstract : Introduction: Lung cancer has the highest mortality of all cancers in the UK and, as such, constitutes a major public health problem. Lung-SEARCH is a UK multi-centre randomised control trial to determine whether screening (annual sputum cytology and if positive, followed by annual CT scanning and bronchoscopy) of smokers with mild COPD improves the detection of lung cancer at early stages when curative treatment is feasible. Acceptability is an ethical requirement of any screening programme. In addition, maximising participation of at-risk groups is key to any successful screening programme. We conducted a qualitative study to answer two questions: Are the screening methods of the Lung Search trial acceptable to patients Why do some people take part and others decline? Methodology: A qualitative study using semi-structured face-to-face and telephone interviews involving three groups of respondents a) those giving an annual sputum sample; b) those undergoing annual bronchoscopy and CT scanning, and c) those who declined participation in the trial. We used the Framework technique to carry out a thematic analysis. Respondent validation was used to strengthen the research findings. Results: 50 interviews were completed (group a: 16, group b: 11; group c: 23). Respondents felt sputum analysis and CT scanning was acceptable. Some recalled a negative experience of bronchoscopy but would not object to future bronchoscopies. The main reasons for declining the trial include travelling for CT scanning and bronchoscopy, negative experiences/perceptions of screening tests, and low perceived susceptibility of lung cancer. There were four main typological behaviours recognised within the declining group: 'too old to be bothered', 'worriers', 'fatalists' and 'avoiders'. Declining patients perceived they were at low risk compared to those taking part. Risk was believed to be related to family history and current health rather than smoking. Conclusion: Whilst screening methods in the Lung-SEARCH trial are largely acceptable to trial participants, strategies to increase acceptability and participation of this at-risk group should include providing tests locally, resolving anxieties concerning screening tests and addressing beliefs of those who underestimate or deny their risk of lung cancer.